Negative electrode sheet, method for manufacturing the same, and use thereof

CN123017865APending Publication Date: 2026-10-30HUIZHOU EVE POWER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611160276.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

常见的负极极片存在内部孔隙结构致密且分布不均的问题,难以实现电解液由表及里快速、均匀地浸润;且负极活性材料自身保液能力较差,高温存储、循环条件下,电解液容易挥发、渗漏,进而导致电池倍率性能下降、循环寿命衰减

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017865A_ABST
    Figure CN123017865A_ABST
Patent Text Reader

Abstract

The application provides a negative electrode sheet, a preparation method and application thereof. The negative electrode sheet comprises a current collector and a negative electrode active layer arranged on the surface of the current collector. The negative electrode active layer comprises a negative electrode active material and composite microspheres. The composite microspheres comprise a core and a coating layer arranged on the surface of the core. The core comprises an inorganic porous material, and the coating layer comprises a polymer. The negative electrode sheet adds the special core-shell structure composite microspheres in the negative electrode active layer, improves the electrolyte immersion rate and liquid retention capacity of the negative electrode sheet, reduces the interface impedance of the negative electrode sheet and the electrolyte, and further improves the cycle life and rate performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of batteries, and in particular to a negative electrode sheet, its preparation method, and its application. Background Technology

[0002] With the rapid development of the new energy industry, the requirements for energy density, cycle life, and safety performance of lithium-ion batteries are becoming increasingly stringent. Common negative electrode sheets suffer from dense and unevenly distributed internal pore structures, making it difficult to achieve rapid and uniform electrolyte wetting from the surface inwards. Furthermore, the negative electrode active material itself has poor liquid retention capacity; under high-temperature storage and cycling conditions, the electrolyte is prone to evaporation and leakage, leading to a decrease in battery rate performance and cycle life. In addition, the interfacial compatibility between the negative electrode active material and the electrolyte in traditional negative electrode sheets is poor, resulting in increased interfacial impedance and internal resistance, affecting the battery's low-temperature performance and fast-charging performance. Existing battery negative electrodes typically use a single inorganic or organic material as a liquid-retaining and lubricating agent, but this usually fails to simultaneously achieve excellent structural support and good long-term liquid retention performance. Summary of the Invention

[0003] In view of this, this application provides a negative electrode sheet, its preparation method and application. The negative electrode sheet improves the electrolyte wetting rate and electrolyte retention capacity of the negative electrode sheet by adding special core-shell structured composite microspheres to the negative electrode active layer, while reducing the interfacial impedance between the negative electrode sheet and the electrolyte, thereby improving the cycle life and rate performance of the battery.

[0004] The first aspect of this application provides a negative electrode sheet, the negative electrode sheet including a current collector and a negative electrode active layer disposed on the surface of the current collector; the negative electrode active layer includes a negative electrode active material and composite microspheres, the composite microspheres including a core and a coating layer disposed on the surface of the core, the core including an inorganic porous material, and the coating layer including a polymer.

[0005] The negative electrode sheet provided in this application introduces composite microspheres with a special core-shell structure into the negative electrode active layer, which can quickly adsorb and effectively store the electrode liquid, improve ion conduction efficiency, reduce the internal resistance of the negative electrode, and also improve the interfacial compatibility between the negative electrode sheet and the electrolyte, as well as the ability to lock in and retain the electrolyte, thereby improving the cycle life and rate performance of the battery.

[0006] In some embodiments of this application, the mass percentage of the composite microspheres in the negative electrode active layer decreases from the side closer to the current collector to the side farther away from the current collector.

[0007] In some embodiments of this application, the particle size Dv50 of the composite microspheres is 60 nm-3100 nm; the particle size distribution index PDI of the composite microspheres is less than or equal to 0.25.

[0008] In some embodiments of this application, the inorganic porous material includes one or more of mesoporous SiO2, boehmite, mesoporous carbon, Al2O3, Li3PO4, and MCM-41 molecular sieve.

[0009] In some embodiments of this application, the particle size Dv50 of the inorganic porous material is 50 nm-3000 nm.

[0010] In some embodiments of this application, the porosity of the inorganic porous material is 65%-90%.

[0011] In some embodiments of this application, the specific surface area of ​​the inorganic porous material is 450 m². 2 / g-1700 m 2 / g.

[0012] In some embodiments of this application, the polymer includes one or more of polyacrylic acid, polyethylene glycol, polyvinylidene fluoride, polyurethane, polyimide, and vinylidene fluoride-hexafluoropropylene copolymer.

[0013] In some embodiments of this application, the thickness of the coating layer is 1 nm-80 nm.

[0014] In some embodiments of this application, the negative electrode active layer includes at least two stacked negative electrode active sublayers; in any two adjacent negative electrode active sublayers, the mass percentage of composite microspheres in the negative electrode active sublayer closer to the current collector is greater than the mass percentage of composite microspheres in the negative electrode active sublayer farther from the current collector.

[0015] In some embodiments of this application, the number of negative electrode active sublayers is 2-4.

[0016] In some embodiments of this application, the composite microspheres in the negative electrode active sublayer closest to the current collector have a mass percentage content of 0.5%-1%; the composite microspheres in the negative electrode active sublayer furthest from the current collector have a mass percentage content of 0.1%-0.25%.

[0017] In some embodiments of this application, the absolute value of the difference in the mass percentage of composite microspheres in any two adjacent negative electrode active sublayers is 0.15%-0.25%.

[0018] In some embodiments of this application, the core particle size of the composite microspheres in the negative electrode active sublayer closest to the current collector is 50 nm-180 nm; the core particle size of the composite microspheres in the negative electrode active sublayer furthest from the current collector is 800 nm-3000 nm.

[0019] In some embodiments of this application, the absolute value of the difference in the core particle size of the composite microspheres in any two adjacent negative electrode active sublayers is 300 nm-500 nm.

[0020] In some embodiments of this application, the thickness of the coating layer of the composite microspheres in the negative electrode active sublayer closest to the current collector is 5 nm-20 nm; the thickness of the coating layer of the composite microspheres in the negative electrode active sublayer furthest from the current collector is 40 nm-80 nm.

[0021] In some embodiments of this application, the absolute value of the difference in thickness between the coating layers of composite microspheres in any two adjacent negative electrode active sublayers is 20 nm-30 nm.

[0022] In some embodiments of this application, the compaction density of the negative electrode sheet is 1.7 g / cm³. 3 -1.8 g / cm 3 .

[0023] In some embodiments of this application, the porosity of the negative electrode sheet is 30%-38%.

[0024] In some embodiments of this application, the saturated liquid absorption capacity of the negative electrode sheet is 0.22 g / g-0.3 g / g.

[0025] In some embodiments of this application, the liquid absorption rate of the negative electrode sheet is 0.45 g / s-0.75 g / s.

[0026] In some embodiments of this application, the negative electrode sheet has a liquid retention rate of 93% or greater at 25°C.

[0027] A second aspect of this application provides a method for preparing a negative electrode sheet, comprising: At least two negative electrode slurries are provided, each of which includes a negative electrode active material and composite microspheres, and the mass content of the composite microspheres in the at least two negative electrode slurries is different; the composite microspheres include a core and a coating layer disposed on the surface of the core, the core includes an inorganic porous material, and the coating layer includes a polymer; The at least two negative electrode slurries are sequentially coated onto the surface of the current collector to obtain a negative electrode active layer, such that the mass percentage of the composite microspheres in the negative electrode active layer decreases from the side closer to the current collector to the side farther away from the current collector.

[0028] A third aspect of this application provides a battery comprising a positive electrode, a negative electrode, a separator and an electrolyte located between the positive electrode and the negative electrode, wherein the negative electrode comprises a negative electrode prepared by the method of the method provided in the first aspect or the method of the method provided in the second aspect.

[0029] The fourth aspect of this application provides an electrical device, which includes the battery provided in the third aspect. Attached Figure Description

[0030] Figure 1 This is a schematic diagram of the composite microspheres in the negative electrode sheet provided in an embodiment of this application.

[0031] Figure 2 This is a schematic diagram of the structure of a negative electrode sheet provided in an embodiment of this application.

[0032] Figure 3 This is a schematic diagram of the structure of a negative electrode sheet provided in another embodiment of this application.

[0033] Figure 4 This is a schematic diagram of the structure of the negative electrode sheet provided in another embodiment of this application.

[0034] Explanation of icon numbers 100-Composite microspheres; 101-Core; 102-Coating layer; 10-Negative electrode sheet; 11-Current collector; 12-Negative active layer; 121-First negative active sublayer; 122-Second negative active sublayer; 123-Third negative active sublayer; 124-Fourth negative active sublayer. Detailed Implementation

[0035] The present application will be further described in detail below with reference to preferred embodiments, but the scope of protection of the present application is not limited to the following specific embodiments.

[0036] In this application, all technical terms have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing specific embodiments only and are not intended to limit the scope of protection of this application.

[0037] With the rapid development of the new energy industry, the requirements for energy density, cycle life, and safety performance of lithium-ion batteries are becoming increasingly stringent. Common negative electrode sheets suffer from dense and unevenly distributed internal pore structures, making it difficult for the electrolyte to rapidly and uniformly penetrate from the surface inwards, easily leading to insufficient wetting within the electrode. Furthermore, negative electrode active materials, such as silicon-based and carbon-based materials, have poor electrolyte retention capabilities. Under high-temperature storage and cycling conditions, the electrolyte easily evaporates and leaks, disrupting the ion transport channels within the electrode, thus causing a decrease in battery rate performance and cycle life. In addition, the interfacial compatibility between the negative electrode active material and the electrolyte in traditional negative electrode sheets is poor. During charge-discharge cycles, a loose solid electrolyte interface (SEI) film easily forms at the interface, repeatedly breaking and reconstructing with changes in electrode volume, consuming a large amount of electrolyte. This, in turn, increases interfacial impedance and internal battery resistance, affecting the battery's low-temperature performance and fast-charging performance. Existing battery anodes typically use a single inorganic or organic material as a liquid retention and lubrication aid, but it is usually difficult to simultaneously achieve excellent structural support and good long-term liquid retention performance.

[0038] This application provides a negative electrode sheet, which includes a current collector and a negative electrode active layer disposed on the surface of the current collector. In embodiments of this application, the negative electrode active layer includes a negative electrode active material and composite microspheres. Figure 2 As shown, the composite microsphere 100 includes a core 101 and a coating layer 102 disposed on the surface of the core 101. The core 101 comprises an inorganic porous material, and the coating layer 102 comprises a polymer. This application introduces composite microspheres with a special core-shell structure into the negative electrode active layer. The inorganic porous material core serves as the structural framework of the composite microsphere, possessing strong mechanical stability and effectively preventing high-temperature deformation. Furthermore, the porous structure of the inorganic porous material allows for rapid adsorption and effective storage of the electrode electrolyte. In addition, the inorganic porous material has a high specific surface area, which can construct good ion transport channels within the negative electrode sheet, improving ion conduction efficiency and reducing the internal resistance of the negative electrode. The polymer coating layer in the composite microsphere enhances the interfacial compatibility between the negative electrode sheet and the electrolyte, and also improves the liquid retention capacity of the composite microsphere. Furthermore, the highly elastic polymer coating layer can effectively buffer the volume expansion of the negative electrode active material, thereby comprehensively improving the cycle life and rate performance of the battery.

[0039] See Figure 1This application provides a negative electrode 10, which includes a current collector 11 and a negative electrode active layer 12 disposed on the surface of the current collector 11. In some embodiments of this application, the negative electrode active layer 12 includes a negative electrode active material and composite microspheres 100. In some embodiments of this application, the mass percentage of composite microspheres 100 in the negative electrode active layer 12 decreases from the side closer to the current collector 11 to the side farther away from the current collector 11. This application further designs a special gradient in the amount of composite microspheres added in the thickness direction of the negative electrode active layer, controlling the content of composite microspheres to decrease from the side closer to the current collector to the side farther away from the current collector, so that the negative electrode achieves a gradient liquid absorption and retention structure in the thickness direction. In the thickness direction of the negative electrode, the composite microsphere content is higher on the side closer to the current collector, which can fully absorb and store electrolyte; the composite microsphere content is lower on the side farther away from the current collector, which can fully optimize the interfacial compatibility between the negative electrode and the electrolyte. Through the above gradient design, a continuous ion channel can be built inside the negative electrode sheet, while the electrolyte can be rapidly and uniformly wetted from the surface to the inside in the thickness direction of the negative electrode sheet, thereby further improving the cycle life and rate performance of the battery.

[0040] In some embodiments of this application, the particle size Dv50 of the composite microspheres 100 is 60 nm-3100 nm. In some specific embodiments, the particle size Dv50 of the composite microspheres 100 can be, for example, 60 nm, 80 nm, 100 nm, 150 nm, 180 nm, 200 nm, 300 nm, 500 nm, 600 nm, 800 nm, 1000 nm, 1500 nm, 2000 nm, 2500 nm, 3000 nm, or 3100 nm. By controlling the particle size of the composite microspheres within the above-mentioned suitable range, the absorption and storage capacity of the composite microspheres for the electrolyte can be further improved, and aggregation of the composite microspheres can be avoided to a certain extent. In this application, the particle size Dv50 is also called the median particle size or average particle size, which refers to the particle size corresponding to the cumulative particle size distribution volume percentage of the sample reaching 50%. In the embodiments of this application, the testing method for particle size Dv50 includes, but is not limited to, laser diffraction.

[0041] In some embodiments of this application, the particle size distribution index (PDI) of the composite microspheres 100 is less than or equal to 0.25. In some specific embodiments, the PDI of the composite microspheres 100 may be, for example, 0.25, 0.24, 0.23, 0.22, 0.21, 0.2, 0.19, 0.18, 0.17, 0.16, 0.15, 0.13, 0.12, 0.1, 0.08, 0.06, or 0.05. In this application, the PDI is a key indicator for measuring the uniformity of particle size distribution; the smaller the value, the more uniform the particle size distribution. In embodiments of this application, the PDI is measured, including but not limited to, by dynamic light scattering methods, specifically by analyzing light intensity fluctuation data to calculate the normalized variance of the particle size distribution.

[0042] In this application, the core 101 comprises an inorganic porous material. In some embodiments of this application, the inorganic porous material includes one or more of mesoporous SiO2, boehmite, mesoporous carbon, Al2O3, Li3PO4, and MCM-41 molecular sieve. In some specific embodiments of this application, the inorganic porous material includes one or more of mesoporous SiO2, boehmite, and mesoporous carbon. By selecting the above-mentioned suitable inorganic porous material as the core, the absorption and storage capacity of the composite microspheres for electrolyte can be further improved, and the mechanical properties of the composite microspheres can also be further enhanced.

[0043] In some embodiments of this application, the particle size Dv50 of the inorganic porous material is 50 nm-3000 nm. In some specific embodiments, the particle size Dv50 of the inorganic porous material can be, for example, 50 nm, 60 nm, 80 nm, 100 nm, 150 nm, 180 nm, 200 nm, 300 nm, 500 nm, 600 nm, 800 nm, 1000 nm, 1500 nm, 2000 nm, 2500 nm, or 3000 nm. By controlling the particle size of the inorganic porous material within the above-mentioned suitable range, the absorption and storage capacity of the composite microspheres for electrolyte can be further improved, and the aggregation of the composite microspheres can be avoided to a certain extent.

[0044] In some embodiments of this application, the porosity of the inorganic porous material is 65%-90%. In some specific embodiments, the porosity of the inorganic porous material can be, for example, 65%, 66%, 68%, 70%, 72%, 74%, 75%, 78%, 80%, 82%, 84%, 85%, 88%, or 90%. In some embodiments of this application, the specific surface area of ​​the inorganic porous material is 450 m². 2 / g-1700 m 2 / g. In some specific embodiments, the specific surface area of ​​the inorganic porous material can be, for example, 450 m². 2 / g、460 m 2 / g、470 m 2 / g、480m 2 / g、490 m 2 / g、500 m 2 / g、600 m 2 / g、800 m 2 / g, 1000 m 2 / g、1200 m 2 / g, 1400 m 2 / g, 1500 m 2 / g、1600 m 2 / g、1700 m 2 / g. By controlling the porosity and specific surface area of ​​the inorganic porous material within the above-mentioned suitable range, the pore volume structure of the composite microspheres can be further improved, thereby further enhancing their adsorption and storage capacity for electrode liquid and maximizing the electrolyte adsorption capacity as much as possible.

[0045] In this application, the coating layer 102 comprises a polymer. In some embodiments of this application, the polymer includes one or more of polyacrylic acid (PAA), polyethylene glycol (PEG), polyvinylidene fluoride (PVDF), polyurethane (PU), polyimide (PI), and PVDF-HFP copolymer. In some specific embodiments of this application, the polymer includes one or more of polyacrylic acid, polyethylene glycol, and polyimide. By selecting the above-mentioned polymers that are more electrolyte-friendly, have higher elasticity, and are more heat-resistant, the interfacial compatibility of the composite microspheres with the electrolyte and the negative electrode active material, as well as the buffering capacity for the expansion of the negative electrode material, can be further improved, and the aggregation of the composite microspheres can be avoided to a certain extent. A dense electrolyte-locking layer can also be formed, reducing the volatilization and loss of the electrolyte at high temperatures, thereby further improving the cycle performance and rate performance of the negative electrode. Furthermore, the above-mentioned polymers can be bonded to the inorganic porous material core through covalent bonds and / or hydrogen bonds, making them less prone to peeling or detachment during battery cycling, further improving the cycle life of the battery.

[0046] In some embodiments of this application, the thickness of the coating layer 102 is 1 nm to 80 nm. In some specific embodiments, the thickness of the coating layer 102 can be, for example, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 8 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, or 80 nm. By controlling the coating layer thickness within the above range, while ensuring sufficient interface buffering capacity, the ion transport resistance can be further reduced.

[0047] In this application, the overlay layer 102 may completely or partially cover the kernel 101. In some embodiments of this application, the overlay layer 102 completely covers the kernel 101. In this application, the overlay layer 102 may continuously or discontinuously cover the kernel 101. In some embodiments of this application, the overlay layer 102 continuously covers the kernel 101.

[0048] In some embodiments of this application, the negative electrode active layer 12 includes at least two stacked negative electrode active sublayers. In some embodiments of this application, in any two adjacent negative electrode active sublayers, the mass percentage of composite microspheres 100 in the negative electrode active sublayer closer to the current collector 11 is greater than the mass percentage of composite microspheres 100 in the negative electrode active sublayer farther from the current collector 11. By specially designing the content of composite microspheres in the thickness direction of the negative electrode active layer, controlling the content of composite microspheres to decrease from the side closer to the current collector to the side farther from the current collector, a gradient liquid absorption and retention structure is achieved in the thickness direction of the negative electrode sheet. In the thickness direction of the negative electrode sheet, the content of composite microspheres is higher on the side closer to the current collector, which can fully absorb and store electrolyte; the content of composite microspheres is lower on the side farther from the current collector, which can fully optimize the interfacial compatibility between the negative electrode sheet and the electrolyte. Through the above gradient design, a continuous ion channel can be built inside the negative electrode sheet, while the electrolyte can be rapidly and uniformly wetted from the surface to the inside in the thickness direction of the negative electrode sheet, thereby improving the cycle life and rate performance of the battery.

[0049] In some embodiments of this application, the number of negative electrode active sublayers is 2-4. Figure 3 As shown, the negative electrode active layer 12 includes two stacked negative electrode active sublayers, namely a first negative electrode active sublayer 121 and a second negative electrode active sublayer 122. In this case, the mass percentage content of the composite microspheres 100 in the first negative electrode active sublayer 121 is greater than the mass percentage content of the composite microspheres 100 in the second negative electrode active sublayer 122. In other embodiments of this application, such as... Figure 1As shown, the negative electrode active layer 12 includes three stacked negative electrode active sublayers, namely a first negative electrode active sublayer 121, a second negative electrode active sublayer 122, and a third negative electrode active sublayer 123. In this case, the mass percentage content of the composite microspheres 100 in the first negative electrode active sublayer 121, the second negative electrode active sublayer 122, and the third negative electrode active sublayer 123 decreases in that order. In some other embodiments of this application, such as... Figure 4 As shown, the negative electrode active layer 12 includes four stacked negative electrode active sublayers, namely the first negative electrode active sublayer 121, the second negative electrode active sublayer 122, the third negative electrode active sublayer 123, and the fourth negative electrode active sublayer 124. At this time, the mass percentage content of composite microspheres 100 in the first negative electrode active sublayer 121, the second negative electrode active sublayer 122, the third negative electrode active sublayer 123, and the fourth negative electrode active sublayer 124 decreases in that order. When the number of active sublayers of the negative electrode is 3-4, the gradient structure of the negative electrode sheet can be further optimized. The negative electrode sheet contains more composite microspheres on the side closer to the current collector in the thickness direction, which can store a large amount of electrolyte, build the underlying ion transport foundation, and provide structural support, buffering the deformation stress of the electrode sheet as a whole. The negative electrode sheet contains a moderate number of composite microspheres in the middle position in the thickness direction, which are evenly dispersed in the middle of the negative electrode sheet. This can effectively build a through ion transport channel, ensuring that the electrolyte can be quickly transported to the interior of the electrode sheet, balancing the liquid retention capacity and ion conduction efficiency of the negative electrode sheet, and maintaining the stability of the electrochemical environment inside the electrode sheet. The negative electrode sheet contains fewer composite microspheres on the side farther from the current collector in the thickness direction, which can further optimize the interfacial compatibility between the negative electrode sheet and the electrolyte and separator, quickly achieve electrolyte wetting of the electrode sheet surface, effectively reduce interfacial impedance, effectively buffer the volume expansion of the negative electrode sheet surface, and inhibit the pulverization and cracking of the electrode sheet. This results in the negative electrode sheet exhibiting excellent comprehensive performance in the thickness direction, with a high-density liquid storage in the inner layer (near the current collector), uniform mass transfer in the middle layer, and a modified interface in the surface layer (away from the current collector). Consequently, the negative electrode sheet possesses both high energy density, excellent electron and ion conduction capability, and excellent overall liquid retention and lubrication effect.

[0050] In some embodiments of this application, the thickness of the negative electrode active layer 12 is 80 μm-90 μm. In some specific embodiments, the thickness of the negative electrode active layer 12 can be, for example, 80 μm, 81 μm, 82 μm, 83 μm, 84 μm, 85 μm, 86 μm, 87 μm, 88 μm, 89 μm, or 90 μm. In some embodiments of this application, the thickness of the negative electrode active sublayer is 12 μm-65 μm. In some specific embodiments, the thickness of the negative electrode active sublayer can be, for example, 12 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, or 65 μm.

[0051] In some embodiments of this application, the current collector 11 is, but is not limited to, copper foil or composite copper foil. In some embodiments of this application, the thickness of the current collector 11 is 4 μm-8 μm. In some specific embodiments, the thickness of the current collector 11 can be, for example, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, or 8 μm. In some embodiments of this application, the mass percentage of composite microspheres 100 in the negative electrode active sublayer closest to the current collector 11 in the negative electrode active layer 12 is 0.5%-1%. In some specific embodiments, the mass percentage of composite microspheres 100 in the negative electrode active sublayer closest to the current collector 11 in the negative electrode active layer 12 can be, for example, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, or 1%. By controlling the content of composite microspheres in the negative electrode active sublayer closest to the current collector within a suitable range, the liquid storage density of the negative electrode sheet in the thickness direction near the current collector region can be further improved, thereby further enhancing the liquid absorption and retention capacity of the negative electrode sheet, and thus further improving the rate performance and cycle life of the battery.

[0052] In some embodiments of this application, the mass percentage of composite microspheres 100 in the negative electrode active sublayer furthest from the current collector 11 in the negative electrode active layer 12 is 0.1%-0.25%. In some specific embodiments, the mass percentage of composite microspheres 100 in the negative electrode active sublayer furthest from the current collector 11 in the negative electrode active layer 12 can be, for example, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, or 0.25%. By controlling the content of composite microspheres in the negative electrode active sublayer furthest from the current collector within a suitable range, the interfacial compatibility between the negative electrode sheet and the electrolyte can be further improved, thereby further reducing the internal resistance of the battery and further improving the low-temperature performance and fast-charging performance of the battery.

[0053] In some embodiments of this application, the difference in mass percentage of composite microspheres 100 between the negative active sublayer closest to the current collector 11 and the negative active sublayer furthest from the current collector 11 in the negative active layer 12 is 0.4%-0.9%. In some specific embodiments, the difference in mass percentage of composite microspheres 100 between the negative active sublayer closest to the current collector 11 and the negative active sublayer furthest from the current collector 11 in the negative active layer 12 can be, for example, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, or 0.9%. By further controlling the above parameters, the liquid absorption and retention gradient in the thickness direction of the negative electrode sheet can be further adjusted, thereby further optimizing the overall performance of the negative electrode sheet.

[0054] In some embodiments of this application, the absolute value of the difference in the mass percentage content of composite microspheres 100 in any two adjacent negative electrode active sublayers of the negative electrode active layer 12 is 0.15%-0.25%. In some specific embodiments, the absolute value of the difference in the mass percentage content of composite microspheres 100 in any two adjacent negative electrode active sublayers of the negative electrode active layer 12 can be, for example, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, or 0.25%. By further controlling the above parameters, the liquid absorption and retention gradient in the thickness direction of the negative electrode sheet can be further adjusted, thereby further optimizing the overall performance of the negative electrode sheet.

[0055] In some embodiments of this application, in any two adjacent negative electrode active sublayers, the particle size of the core 101 of the composite microspheres 100 in the negative electrode active sublayer closer to the current collector 11 is larger than the particle size of the core 101 of the composite microspheres 100 in the negative electrode active sublayer farther from the current collector 11. By performing a special gradient design on the core particle size of the composite microspheres in the thickness direction of the negative electrode active layer, the liquid absorption and retention gradient of the negative electrode sheet in the thickness direction can be further controlled, further realizing the hierarchical filling of the pores inside the negative electrode sheet and precise functional zoning, and further improving the cycle life and rate performance of the battery.

[0056] In some embodiments of this application, the particle size Dv50 of the core 101 of the composite microspheres 100 in the negative electrode active sublayer closest to the current collector 11 in the negative electrode active layer 12 is 50 nm-180 nm. In some specific embodiments, the particle size Dv50 of the core 101 of the composite microspheres 100 in the negative electrode active sublayer closest to the current collector 11 in the negative electrode active layer 12 can be, for example, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, or 180 nm. By controlling the core particle size of the composite microspheres in the negative electrode active sublayer closest to the current collector within a suitable range, the liquid storage density of the negative electrode sheet in the thickness direction near the current collector region can be further improved, thereby further enhancing the liquid absorption and retention capacity of the negative electrode sheet, and thus further improving the rate performance and cycle life of the battery.

[0057] In some embodiments of this application, the particle size Dv50 of the core 101 of the composite microspheres 100 in the negative electrode active sublayer furthest from the current collector 11 in the negative electrode active layer 12 is 800 nm-3000 nm. In some specific embodiments, the particle size Dv50 of the core 101 of the composite microspheres 100 in the negative electrode active sublayer furthest from the current collector 11 in the negative electrode active layer 12 can be, for example, 800 nm, 900 nm, 1000 nm, 1200 nm, 1400 nm, 1500 nm, 1600 nm, 1800 nm, 2000 nm, 2200 nm, 2400 nm, 2500 nm, 2600 nm, 2800 nm, or 3000 nm.

[0058] In some embodiments of this application, the particle size Dv50 of the core 101 of the composite microspheres 100 in the negative active sublayer closest to the current collector 11 and the negative active sublayer furthest from the current collector 11 in the negative active layer 12 is 1500 nm-1900 nm. In some specific embodiments, the particle size Dv50 of the core 101 of the composite microspheres 100 in the negative active sublayer furthest from the current collector 11 in the negative active layer 12 can be, for example, 1500 nm, 1550 nm, 1600 nm, 1650 nm, 1700 nm, 1750 nm, 1800 nm, 1850 nm, or 1900 nm.

[0059] In some embodiments of this application, the absolute value of the difference in particle size Dv50 between the cores 101 of the composite microspheres 100 in any two adjacent negative electrode active sublayers of the negative electrode active layer 12 is 300 nm to 500 nm. In some specific embodiments, the absolute value of the difference in particle size Dv50 between the cores 101 of the composite microspheres in any two adjacent negative electrode active sublayers of the negative electrode active layer 12 can be, for example, 300 nm, 320 nm, 340 nm, 350 nm, 360 nm, 380 nm, 400 nm, 420 nm, 440 nm, 450 nm, 460 nm, 480 nm, or 500 nm.

[0060] In some embodiments of this application, in any two adjacent negative electrode active sublayers, the thickness of the coating layer of the composite microspheres 100 in the negative electrode active sublayer closer to the current collector 11 is less than the thickness of the coating layer of the composite microspheres 100 in the negative electrode active sublayer farther from the current collector 11. By designing a special gradient in the thickness direction of the coating layer in the negative electrode active layer, the liquid retention capacity of the negative electrode sheet and the buffering effect on the expansion of the negative electrode sheet can be further improved.

[0061] In some embodiments of this application, the thickness of the coating layer 102 of the composite microspheres 100 in the negative active sublayer closest to the current collector 11 in the negative active layer 12 is 5 nm-20 nm. In some specific embodiments, the thickness of the coating layer 102 of the composite microspheres 100 in the negative active sublayer closest to the current collector 11 in the negative active layer 12 can be, for example, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 12 nm, 14 nm, 15 nm, 16 nm, 18 nm, or 20 nm. By controlling the thickness of the coating layer in the negative active sublayer closest to the current collector within a suitable range, the ion conductivity of the negative electrode sheet in the thickness direction, particularly in the region near the current collector, can be further improved.

[0062] In some embodiments of this application, the thickness of the coating layer 102 of the composite microspheres 100 in the negative electrode active sublayer furthest from the current collector 11 in the negative electrode active layer 12 is 40 nm-80 nm. In some specific embodiments, the thickness of the coating layer 102 of the composite microspheres 100 in the negative electrode active sublayer furthest from the current collector 11 in the negative electrode active layer 12 can be, for example, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, or 80 nm. By controlling the thickness of the coating layer in the negative electrode active sublayer furthest from the current collector within a suitable range, the liquid-locking ability of the negative electrode sheet near the electrolyte surface and the suppression effect on the volume expansion of the negative electrode active material can be further improved.

[0063] In some embodiments of this application, the thickness difference of the coating layer 102 of the composite microspheres 100 in the negative electrode active layer 12 furthest from the current collector 11 and the negative electrode active sublayer closest to the current collector 11 is 35 nm to 60 nm. In some specific embodiments, the thickness difference of the coating layer 102 of the composite microspheres 100 in the negative electrode active layer 12 furthest from the current collector 11 and the negative electrode active sublayer closest to the current collector 11 can be, for example, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, or 60 nm.

[0064] In some embodiments of this application, the absolute value of the difference in thickness of the coating layer 102 of the composite microspheres 100 in any two adjacent negative electrode active sublayers of the negative electrode active layer 12 is 20 nm to 30 nm. In some specific embodiments, the absolute value of the difference in thickness of the coating layer 102 of the composite microspheres 100 in any two adjacent negative electrode active sublayers of the negative electrode active layer 12 can be, for example, 20 nm, 21 nm, 22 nm, 23 nm, 24 nm, 25 nm, 26 nm, 27 nm, 28 nm, 29 nm, or 30 nm.

[0065] In some embodiments of this application, the compaction density of the negative electrode sheet 10 is 1.7 g / cm³. 3 -1.8 g / cm 3 In some specific embodiments, the compaction density of the negative electrode 10 can be, for example, 1.7 g / cm³. 3 1.71 g / cm 3 1.72 g / cm 3 1.73g / cm 3 1.74 g / cm 3 1.75 g / cm 3 1.76 g / cm 3 1.77 g / cm 3 1.78 g / cm 3 1.79 g / cm 3 1.8 g / cm 3 In some embodiments of this application, the porosity of the negative electrode 10 is 30%-38%. In some specific embodiments, the porosity of the negative electrode 10 may be, for example, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, or 38%. The negative electrode provided by this application has excellent electrolyte wetting effect and electrolyte retention capacity within the above-mentioned suitable ranges of compaction density and porosity.

[0066] In some embodiments of this application, the saturated liquid absorption capacity of the negative electrode 10 is 0.22 g / g to 0.3 g / g. In this application, the saturated liquid absorption capacity refers to the maximum mass of liquid that each gram of the negative electrode 10 can absorb and retain when fully saturated. In some specific embodiments, the saturated liquid absorption capacity of the negative electrode 10 can be, for example, 0.22 g / g, 0.23 g / g, 0.24 g / g, 0.25 g / g, 0.26 g / g, 0.27 g / g, 0.28 g / g, 0.29 g / g, or 0.3 g / g. In this embodiment of the application, the saturated liquid absorption capacity is not limited to the following method: weigh the negative electrode sheet dried to constant weight and record it as m0 (g), then completely immerse the negative electrode sheet in the standard electrolyte and let it stand until no bubbles are released, remove the negative electrode sheet and gently wipe the surface free electrolyte with filter paper, weigh it again and record it as m1 (g), and calculate the saturated liquid absorption capacity using the formula: saturated liquid absorption capacity = (m1-m0) / m0.

[0067] In some embodiments of this application, the liquid retention rate of the negative electrode 10 at 25°C is greater than or equal to 93%. In some specific embodiments, the liquid retention rate of the negative electrode 10 at 25°C can be, for example, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, or 97%. In some embodiments of this application, the liquid retention rate of the negative electrode 10 at 25°C is greater than or equal to 95%. In the embodiments of this application, the liquid retention rate is not limited to being measured by the following method, where m0 and m1 are measured in the same way as m0 and m1 in the above formula for saturated liquid absorption. After the negative electrode is saturated with liquid, it is placed in a constant temperature open environment at 25°C for 24 hours. After wiping off the electrolyte deposited on the surface, it is weighed and recorded as m2. The liquid retention rate is calculated by the formula: Liquid retention rate = (m2-m0) / (m1-m0)×100%.

[0068] In some embodiments of this application, the liquid absorption rate of the negative electrode 10 is 0.45 g / s to 0.75 g / s. In some specific embodiments, the liquid absorption rate of the negative electrode 10 may be, for example, 0.45 g / s, 0.46 g / s, 0.48 g / s, 0.5 g / s, 0.52 g / s, 0.55 g / s, 0.58 g / s, 0.6 g / s, 0.62 g / s, 0.65 g / s, 0.68 g / s, 0.7 g / s, 0.72 g / s, or 0.75 g / s. In this embodiment of the application, the liquid absorption rate can be measured by, but is not limited to, the following method. The measurement methods of m0 and m1 are the same as those of m0 and m1 in the above formula for saturated liquid absorption. The negative electrode is completely immersed in the standard electrolyte and left to stand until no bubbles are precipitated. The time required for the negative electrode to come into contact with the electrolyte until no visible bubbles are precipitated on the surface of the negative electrode is recorded as t (s). The liquid absorption rate is calculated by the formula: Liquid absorption rate = (m1-m0) / t.

[0069] The negative electrode sheet provided in this application achieves a gradient liquid retention and wetting structure in the thickness direction of the negative electrode sheet by adding special core-shell structured composite microspheres to the negative electrode active layer and controlling the content change of these microspheres in the negative electrode active layer. This improves the electrolyte wetting rate and liquid retention capacity of the negative electrode sheet while reducing the interfacial impedance between the negative electrode sheet and the electrolyte, thereby improving the cycle life and rate performance of the battery.

[0070] This application also provides a method for preparing a negative electrode sheet, comprising: S101. Provide at least two negative electrode slurries, each of the negative electrode slurries comprising a negative electrode active material and composite microspheres, and the mass content of the composite microspheres in the at least two negative electrode slurries is different; the composite microspheres comprise a core and a coating layer disposed on the surface of the core, the core comprising an inorganic porous material, and the coating layer comprising a polymer; S102. The at least two negative electrode slurries are sequentially coated on the surface of the current collector to obtain a negative electrode active layer, such that the mass percentage of the composite microspheres in the negative electrode active layer decreases from the side closer to the current collector to the side farther away from the current collector.

[0071] In step S101, the number of types of negative electrode slurry is greater than or equal to two. In some embodiments of this application, the number of types of negative electrode slurry may be, for example, two, three, or four.

[0072] In some embodiments of this application, the composite microspheres may be, but are not limited to, prepared by sol-gel in-situ polymerization. Specifically, the preparation method of the composite microspheres may be, for example, as follows: dispersing inorganic porous materials in a mixed solvent of ethanol and water (ethanol to water mass ratio of 4:1), ultrasonically dispersing until uniform; adding organic monomers and initiators, adjusting the pH value to 3-5, hydrolyzing and condensing at 25°C; curing at 70°C, washing, and vacuum drying to obtain composite microspheres. The above preparation method is simple, leaves almost no impurity residue, and is suitable for large-scale production. In some specific embodiments, the initiator includes, but is not limited to, azobisisobutyramidine hydrochloride (AIBA).

[0073] In this application, the negative electrode active material can be any negative electrode active material known in the art for use in lithium-ion batteries, including but not limited to one or more of carbon-based, silicon-based, tin-based, and lithium metal negative electrode active materials. In some embodiments, the carbon-based negative electrode active material may include, for example, one or more of graphite, carbon fiber, hard carbon, soft carbon, mesophase carbon composite microspheres, and graphene; the silicon-based negative electrode active material may include, for example, one or more of elemental silicon, silicon carbide, silicon oxide and silicon metal compound, and composite silicon materials; the tin-based negative electrode active material may include, for example, one or more of elemental tin, tin carbide, tin oxide, and tin metal compound. In this application, the negative electrode active material includes, but is not limited to, the examples described above. In some specific embodiments of this application, the negative electrode active material includes silicon-based negative electrode active materials.

[0074] In some embodiments of this application, the mass percentage of the negative electrode active material in the negative electrode slurry is 92%-97%. In some specific embodiments, the mass percentage of the negative electrode active material in the negative electrode slurry may be, for example, 92%, 93%, 94%, 95%, 96%, or 97%. In some embodiments of this application, the mass percentage of the composite microspheres in the negative electrode slurry is 0.1%-1%. In some specific embodiments, the mass percentage of the composite microspheres in the negative electrode slurry may be, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1%.

[0075] In some embodiments of this application, the negative electrode slurry further includes a conductive agent and a binder. In these embodiments, the conductive agent can be any conductive agent known in the art. In some embodiments, the conductive agent can be, for example, one or more of Super P-Li, SP (Super P, conductive carbon black), acetylene black, graphene, and carbon nanotubes. In these embodiments, the binder can be any binder known in the art. In some embodiments, the binder can be, for example, one or more of styrene-butadiene rubber and polyvinylidene fluoride.

[0076] In some embodiments of this application, the mass percentage of the conductive agent in the negative electrode slurry is 1%-3%. In some specific embodiments, the mass percentage of the conductive agent in the negative electrode slurry may be, for example, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, or 3%. In some embodiments of this application, the mass percentage of the binder in the negative electrode slurry is 2%-4%. In some specific embodiments, the mass percentage of the binder in the negative electrode slurry may be, for example, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.5%, 3.6%, 3.8%, or 4%.

[0077] In some embodiments of this application, the negative electrode slurry further includes a thickener, which can be any thickener known in the art. In some embodiments of this application, the thickener may be, for example, sodium hydroxycellulose.

[0078] In step S102, depending on the actual application requirements, the negative electrode slurry can be coated on one side of the current collector or on both sides of the current collector.

[0079] In some embodiments of this application, after the negative electrode slurry is sequentially coated onto the surface of the current collector, it is further subjected to drying, rolling, and slicing to obtain the negative electrode sheet.

[0080] The negative electrode preparation method provided in this application is simple, compatible with existing electrode preparation processes, and requires no new equipment or adjustments to core procedures, making it suitable for large-scale industrial production. This preparation method utilizes a multi-layer coating technique to achieve a gradient variation in the content of composite microspheres in the negative electrode active layer along a direction perpendicular to the current collector surface. This, in turn, results in a gradient variation in the electrolyte absorption and retention capacity of the negative electrode along the same direction. The negative electrode prepared using this method exhibits good electrolyte absorption and retention capacity and good interfacial compatibility with the electrolyte, resulting in a longer battery cycle life and better overall electrochemical performance.

[0081] This application also provides a battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte located between the positive and negative electrodes. The negative electrode comprises the negative electrode described above. In embodiments of this application, the battery includes, but is not limited to, a lithium-ion battery. In some embodiments of this application, the positive electrode active material in the positive electrode is, but is not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium phosphates with an olivine structure. In embodiments of this application, the separator is, but is not limited to, a composite membrane of one or more of polyethylene, polypropylene, and polyvinylidene fluoride.

[0082] This application also provides an electrical device that includes the battery described above. This electrical device may be, for example, an electric vehicle, a mobile phone, a tablet computer, a laptop computer, a wearable device (watch, bracelet), a digital camera, etc.

[0083] The present application will be further described below with reference to several embodiments: Example 1 (1) Take 10 g of mesoporous SiO2 with hydroxyl-activated surface treatment (particle size Dv50 is 500 nm, porosity is 75%, specific surface area is 600 m²) 2 / g), dispersed in 100 mL of a mixed solvent of ethanol and water (ethanol to water mass ratio of 4:1), and sonicated for 40 min; 15 g of acrylic acid monomer was added dropwise at a low speed of 0.5 mL / min, and 0.5 g of ammonium persulfate was added simultaneously. The stirring speed of the system was controlled at 300 r / min. After the addition was completed, the reaction was carried out at 70℃ for 4 h; after the reaction was completed, the product was centrifuged and washed with deionized water multiple times to remove unreacted monomers and residual impurities. Then it was placed in a vacuum oven at 80℃ for 6 h to obtain a PAA coating layer on the surface of the mesoporous SiO2 core. The coating layer thickness was 30 nm, and the composite microspheres SiO2@PAA were obtained. The Dv50 of the composite microspheres was 560 nm, and the PDI of the composite microspheres was 0.18. (2) The negative electrode active material silicon carbide graphite, composite microspheres SiO2@PAA, conductive agent SP, thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) are mixed with deionized water at a mass ratio of 96.05:0.55:1:0.9:1.5 to obtain the first negative electrode slurry, which is used for the subsequent preparation of the first negative electrode active sublayer; The negative electrode active material silicon-carbon graphite, composite microspheres SiO2@PAA, conductive agent SP, thickener CMC, and binder SBR were mixed with deionized water at a mass ratio of 96.25:0.35:1:0.9:1.5 to obtain a second negative electrode slurry, which was used to prepare the second negative electrode active sublayer in the subsequent process. The negative electrode active material silicon-carbon graphite, composite microspheres SiO2@PAA, conductive agent SP, thickener CMC, and binder SBR were mixed with deionized water at a mass ratio of 96.5:0.1:1:0.9:1.5 to obtain a third negative electrode slurry, which was used to prepare the third negative electrode active sublayer in the subsequent process. A first negative electrode slurry, a second negative electrode slurry, and a third negative electrode slurry are sequentially coated onto the surface of a current collector copper foil. After drying, the slurry is rolled to obtain a negative electrode sheet. The negative electrode sheet comprises a first negative electrode active sublayer, a second negative electrode active sublayer, and a third negative electrode active sublayer. The thickness of each of the three negative electrode active sublayers is 26.3 μm, and the compaction density of the negative electrode sheet is 1.7 g / cm³.3 .

[0084] Example 2 (1) Same as Example 1; (2) The anode active material silicon carbide graphite, composite microspheres SiO2@PAA, conductive agent SP, thickener CMC, and binder SBR are mixed with deionized water at a mass ratio of 96.05:0.55:1:0.9:1.5 to obtain the first anode slurry, which is used to prepare the first anode active sublayer in the subsequent process. The negative electrode active material silicon-carbon graphite, composite microspheres SiO2@PAA, conductive agent SP, thickener CMC, and binder SBR were mixed with deionized water at a mass ratio of 96.5:0.1:1:0.9:1.5 to obtain a second negative electrode slurry, which was used to prepare the second negative electrode active sublayer in the subsequent process. A first negative electrode slurry and a second negative electrode slurry are sequentially coated onto the surface of the current collector copper foil. After drying, the coating is rolled to obtain a negative electrode sheet. The negative electrode sheet includes a first negative electrode active sublayer and a second negative electrode active sublayer, both with a thickness of 39.45 μm. The compaction density of the negative electrode sheet is 1.7 g / cm³. 3 .

[0085] Example 3 (1) Same as Example 1; (2) The anode active material silicon carbide graphite, composite microspheres SiO2@PAA, conductive agent SP, thickener CMC, and binder SBR are mixed with deionized water at a mass ratio of 96.05:0.55:1:0.9:1.5 to obtain the first anode slurry, which is used to prepare the first anode active sublayer in the subsequent process. The negative electrode active material silicon-carbon graphite, composite microspheres SiO2@PAA, conductive agent SP, thickener CMC, and binder SBR were mixed with deionized water at a mass ratio of 96.2:0.4:1:0.9:1.5 to obtain a second negative electrode slurry, which was used to prepare the second negative electrode active sublayer in the subsequent process. The negative electrode active material silicon-carbon graphite, composite microspheres SiO2@PAA, conductive agent SP, thickener CMC, and binder SBR were mixed with deionized water at a mass ratio of 96.35:0.25:1:0.9:1.5 to obtain the third negative electrode slurry, which was used to prepare the third negative electrode active sublayer in the subsequent process. The negative electrode active material silicon-carbon graphite, composite microspheres SiO2@PAA, conductive agent SP, thickener CMC, and binder SBR were mixed with deionized water at a mass ratio of 96.5:0.1:1:0.9:1.5 to obtain the fourth negative electrode slurry, which was used to prepare the fourth negative electrode active sublayer in the subsequent process. A first negative electrode slurry, a second negative electrode slurry, a third negative electrode slurry, and a fourth negative electrode slurry are sequentially coated on the surface of the current collector copper foil. The negative electrode sheet includes a first negative electrode active sublayer, a second negative electrode active sublayer, a third negative electrode active sublayer, and a fourth active sublayer. The thickness of each of the first, second, third, and fourth active sublayers is 21.25 μm. After drying, the negative electrode sheet is rolled to obtain a compacted density of 1.7 g / cm³. 3 .

[0086] Example 4 (1) Same as Example 1; (2) The negative electrode active material silicon carbide graphite, composite microspheres SiO2@PAA, conductive agent SP, thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) are mixed with deionized water at a mass ratio of 96.3:0.3:1:0.9:1.5 to obtain the first negative electrode slurry, which is used to prepare the first negative electrode active sublayer in the subsequent process. The negative electrode active material silicon-carbon graphite, composite microspheres SiO2@PAA, conductive agent SP, thickener CMC, and binder SBR were mixed with deionized water at a mass ratio of 95.8:0.8:1:0.9:1.5 to obtain a second negative electrode slurry, which was used to prepare the second negative electrode active sublayer in the subsequent process. The negative electrode active material silicon-carbon graphite, composite microspheres SiO2@PAA, conductive agent SP, thickener CMC, and binder SBR were mixed with deionized water at a mass ratio of 96.15:0.45:1:0.9:1.5 to obtain a third negative electrode slurry, which was used to prepare the third negative electrode active sublayer in the subsequent process. A first negative electrode slurry, a second negative electrode slurry, and a third negative electrode slurry are sequentially coated onto the surface of a current collector copper foil. After drying, the slurry is rolled to obtain a negative electrode sheet. The negative electrode sheet comprises a first negative electrode active sublayer, a second negative electrode active sublayer, and a third negative electrode active sublayer. The thickness of each of the three negative electrode active sublayers is 26.3 μm, and the compaction density of the negative electrode sheet is 1.7 g / cm³. 3 .

[0087] Example 5 (1) Take 10 g of porous Al2O3 with hydroxyl-activated surface (particle size Dv50 of 500 nm, porosity of 72%, specific surface area of ​​680 m² / g), disperse it in 100 mL of a mixed solvent of ethanol and water (mass ratio of ethanol to water of 4:1), sonicate for 40 min to make it fully and uniformly dispersed; add 16 g of vinylidene fluoride monomer and 0.52 g of initiator azobisisobutyramidine hydrochloride (AIBA), and react at a constant temperature of 70℃ for 4 h; after the reaction, centrifuge the product and wash it with deionized water several times to remove unreacted monomers and residual impurities, and then dry it in a vacuum oven at 80℃ for 6 h to obtain a PVDF coating layer on the surface of the porous Al2O3 core. The coating layer thickness is 30 nm, and composite microspheres Al2O3@PVDF are obtained. The Dv50 of the composite microspheres is 560 nm, and the particle size distribution index (PDI) of the composite microspheres is 0.18. (2) The negative electrode active material silicon carbon graphite, composite microspheres Al2O3@PVDF, conductive agent SP, thickener CMC, and binder SBR are mixed with deionized water at a mass ratio of 96.05:0.55:1:0.9:1.5 to obtain the first negative electrode slurry, which is used to prepare the first negative electrode active sublayer.

[0088] The negative electrode active material silicon-carbon graphite, composite microspheres Al2O3@PVDF, conductive agent SP, thickener CMC, and binder SBR were mixed with deionized water at a mass ratio of 96.25:0.35:1:0.9:1.5 to obtain a second negative electrode slurry, which was used to prepare the second negative electrode active sublayer. The negative electrode active material silicon-carbon graphite, composite microspheres Al2O3@PVDF, conductive agent SP, thickener CMC, and binder SBR were mixed with deionized water at a mass ratio of 96.5:0.1:1:0.9:1.5 to obtain a third negative electrode slurry, which was used to prepare the third negative electrode active sublayer. A first negative electrode slurry, a second negative electrode slurry, and a third negative electrode slurry are sequentially coated onto the surface of a current collector copper foil. After drying, the slurry is rolled to obtain a negative electrode sheet. The negative electrode sheet comprises a first negative electrode active sublayer, a second negative electrode active sublayer, and a third negative electrode active sublayer. The thickness of each of the three negative electrode active sublayers is 26.3 μm, and the compaction density of the negative electrode sheet is 1.7 g / cm³. 3 .

[0089] Example 6 (1) Take 10 g of mesoporous SiO2 with hydroxyl-activated surface treatment (particle size Dv50 is 150 nm, porosity is 72%, specific surface area is 680 m²) 2 / g), dispersed in 100 mL of a mixed solvent of ethanol and water (ethanol to water mass ratio of 4:1), and sonicated for 40 min; 15 g of acrylic acid monomer was added dropwise at a low speed of 0.5 mL / min, and 0.5 g of ammonium persulfate was added simultaneously. The stirring speed of the system was controlled at 200 r / min. After the addition was completed, the reaction was carried out at 70℃ for 4 h; after the reaction was completed, the product was centrifuged and washed with deionized water multiple times to remove unreacted monomers and residual impurities. Then it was placed in a vacuum oven at 80℃ for 6 h to obtain a PAA coating layer on the surface of the mesoporous SiO2 core. The coating layer thickness was 15 nm, and the first composite microsphere SiO2@PAA was obtained. The Dv50 of the second composite microsphere was 180 nm, and the PDI of the first composite microsphere was 0.18. Take 10 g of mesoporous SiO2 with hydroxyl-activated surface treatment (particle size Dv50 of 550 nm, porosity of 72%, specific surface area of ​​680 m²). 2 / g), dispersed in 100 mL of a mixed solvent of ethanol and water (ethanol to water mass ratio of 4:1), and sonicated for 40 min; 15 g of acrylic acid monomer was added dropwise at a low speed of 0.5 mL / min, and 0.5 g of ammonium persulfate was added simultaneously. The system was stirred at 400 r / min and reacted at 70℃ for 4 h; after the reaction, the product was centrifuged and washed multiple times with deionized water to remove unreacted monomers and residual impurities, and then dried in a vacuum oven at 80℃ for 6 h to obtain a PAA coating layer on the surface of the mesoporous SiO2 core. The coating layer thickness was 40 nm, and the second composite microsphere SiO2@PAA was obtained. The Dv50 of the second composite microsphere was 630 nm, and the PDI of the second composite microsphere was 0.18. Take 10 g of mesoporous SiO2 with hydroxyl-activated surface treatment (particle size Dv50 of 1500 nm, porosity of 72%, specific surface area of ​​680 m²) 2 / g), dispersed in 100 mL of a mixed solvent of ethanol and water (ethanol to water mass ratio of 4:1), and sonicated for 40 min; 15 g of acrylic acid monomer was added dropwise at a low speed of 0.5 mL / min, and 0.5 g of ammonium persulfate was added simultaneously. The system was stirred at 550 r / min and reacted at 70℃ for 4 h; after the reaction, the product was centrifuged and washed multiple times with deionized water to remove unreacted monomers and residual impurities, and then dried in a vacuum oven at 80℃ for 6 h to obtain a PAA coating layer on the surface of the mesoporous SiO2 core. The coating layer thickness was 65 nm, and the third composite microsphere SiO2@PAA was obtained. The Dv50 of the third composite microsphere was 1630 nm, and the particle size distribution index (PDI) of the third composite microsphere was 0.20. (2) The anode active material silicon carbide graphite, the first composite microsphere SiO2@PAA, the conductive agent SP, the thickener CMC, and the binder SBR are mixed with deionized water at a mass ratio of 96.05:0.55:1:0.9:1.5 to obtain the first anode slurry, which is used for the subsequent preparation of the first anode active sublayer. The negative electrode active material silicon-carbon graphite, the second composite microspheres SiO2@PAA, the conductive agent SP, the thickener CMC, and the binder SBR were mixed with deionized water at a mass ratio of 96.25:0.35:1:0.9:1.5 to obtain the second negative electrode slurry, which was used to prepare the second negative electrode active sublayer in the subsequent process. The negative electrode active material silicon-carbon graphite, the third composite microspheres SiO2@PAA, the conductive agent SP, the thickener CMC, and the binder SBR were mixed with deionized water at a mass ratio of 96.5:0.1:1:0.9:1.5 to obtain the third negative electrode slurry, which was used to prepare the third negative electrode active sublayer in the subsequent process. A first negative electrode slurry, a second negative electrode slurry, and a third negative electrode slurry are sequentially coated onto the surface of a current collector copper foil. After drying, the slurry is rolled to obtain a negative electrode sheet. The negative electrode sheet comprises a first negative electrode active sublayer, a second negative electrode active sublayer, and a third negative electrode active sublayer. The thickness of each of the three negative electrode active sublayers is 26.3 μm, and the compaction density of the negative electrode sheet is 1.7 g / cm³. 3 .

[0090] Example 7 (1) Same as Example 1; (2) The negative electrode active material silicon carbide graphite, composite microspheres SiO2@PAA, conductive agent SP, thickener CMC, and binder SBR are mixed with deionized water at a mass ratio of 96.48:0.52:1:1:1 to obtain a negative electrode slurry, which is used for subsequent preparation of the negative electrode active layer. A negative electrode slurry is coated onto the surface of a current collector copper foil, dried, and then rolled to obtain a negative electrode sheet. The negative electrode sheet includes a negative electrode active layer with a thickness of 78.9 μm and a compaction density of 1.7 g / cm³. 3 .

[0091] Comparative Example 1 The only difference from Example 1 is that the composite microspheres SiO2@PAA are replaced with mesoporous SiO2 (particle size Dv50 of 500 nm, porosity of 75%, and specific surface area of ​​600 m²). 2 / g.

[0092] Electrode performance testing Interface resistance: A four-probe resistance tester was used. The test environment temperature was 25℃ and the relative humidity was 50%±5%. The test steps were as follows: The negative electrode sheets prepared in Examples 1-7 and Comparative Example 1 were cut into flat and wrinkle-free standard samples to ensure that the test area surface was clean, dust-free, and free of oxide layer; the sample was placed horizontally on the test table so that the four probes were in close vertical contact with the electrode surface and the probe pressure was kept uniform; the equipment was started and the electrode interface resistance value was read directly; five different locations were selected for each sample for repeated testing, and the average value was taken after removing abnormal data. The results are shown in Table 1.

[0093] 30-minute immersion climbing height: The negative electrode sheets prepared in Examples 1-7 and Comparative Example 1 were cut into regular strip-shaped samples to obtain electrode strips with a length of 25 cm and a width of 5 cm; the electrode strips were vertically fixed on the fixture, ensuring that their lower end face was horizontal; a container filled with electrolyte (the lithium salt in the electrolyte was 1) was placed in the fixture. A transparent tank containing mol / L LiPF6, with a solvent of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a mass ratio of 2:3:5, and an electrolyte including 1% vinylene carbonate (VC) and 0.5% fluoroethylene carbonate (FEC), was placed directly below the electrode strip. The tank position was precisely adjusted using a precision moving platform so that the lower end of the electrode strip was in contact with the electrolyte surface. A high-speed camera was simultaneously triggered to automatically record the process of the electrolyte leading edge climbing vertically upward along the electrode strip. Image analysis software was used to automatically identify and track the position of the electrolyte leading edge, and to generate and record the relationship curve between the climbing height (h) and time (t) (i.e., the ht curve) in real time. The immersion climbing height at 30 min was also recorded. The results are shown in Table 1.

[0094] Battery performance test A positive electrode slurry was prepared by uniformly mixing lithium iron phosphate (the positive electrode active material), polyvinylidene fluoride (PVDF) (the binder), conductive carbon black (SP) (the conductive agent), and polyoxyethylene ether (the dispersant) with deionized water at a mass ratio of 97.5:1.4:0.9:0.2. The positive electrode slurry was then coated onto the surface of an aluminum foil current collector, dried, and rolled to obtain a positive electrode sheet. The compacted density of the positive electrode sheet was 2.65 g / cm³. 3 .

[0095] The negative electrode sheets prepared in Examples 1-7 and Comparative Example 1, together with the above-mentioned positive electrode sheet and separator, were assembled into a battery cell. An electrolyte (the electrolyte composition was the same as that in the 30-minute immersion climb height test) was injected, and the sample battery cell was obtained after the electrolyte was dissolved and compatible.

[0096] 45℃ Cyclic Capacity Retention Rate: The prepared sample cells were transferred to a constant temperature test chamber set at 45℃±1℃ and left to stand for 2 hours. Under constant temperature conditions, continuous charge-discharge cycle tests were conducted with a constant current of 1C within a voltage range of 2.5V to 3.8V. The first discharge capacity and the discharge capacity of the 1000th cycle were recorded. The 45℃ cycle capacity retention rate was calculated using the following formula: 45℃ cycle capacity retention rate (%) = (discharge capacity of the 1000th cycle / discharge capacity of the first cycle) × 100%. The calculated results are shown in Table 1.

[0097] Table 1

[0098] As can be seen from the data of Examples 1-7 and Comparative Example 1 in Table 1, compared with Examples 1-7, the mesoporous SiO2 surface of the negative electrode sheet of Comparative Example 1 does not have a polymer coating layer, the interface resistance of the negative electrode sheet is larger, the 30 min immersion climb height of the electrode sheet is lower, the wettability of the electrolyte is worse, and the 45℃ cycle capacity retention rate is also significantly reduced.

[0099] Data from Examples 1-7 show that, compared to Example 7, Examples 1-6, through further designing the negative electrode active sublayer and changing the mass of the composite microspheres in different negative electrode active sublayers, can further improve the electrolyte wetting rate of the negative electrode sheet, reduce the interfacial impedance between the negative electrode sheet and the electrolyte, and thus improve the cycle performance of the battery. Furthermore, data from Examples 1-6 show that by further designing the number of negative electrode active sublayers, the core of the composite microspheres in different negative electrode active sublayers, and the coating thickness, the liquid absorption and retention capacity and overall electrochemical performance of the negative electrode sheet can be further improved.

[0100] The preferred embodiments have been described in detail above, but the present invention is not limited to the specific implementation methods described above. Those skilled in the art can make various specific modifications under the guidance of this application without departing from the scope of protection of this application, and these modifications all fall within the scope of protection of the present invention.

Claims

1. A negative electrode sheet, characterized in that, The negative electrode sheet includes a current collector and a negative electrode active layer disposed on the surface of the current collector; the negative electrode active layer includes a negative electrode active material and composite microspheres, the composite microspheres include a core and a coating layer disposed on the surface of the core, the core includes an inorganic porous material, and the coating layer includes a polymer.

2. The negative electrode sheet as described in claim 1, characterized in that, In the negative electrode active layer, the mass percentage of the composite microspheres decreases from the side closer to the current collector to the side farther away from the current collector.

3. The negative electrode sheet as described in claim 1 or 2, characterized in that, The particle size Dv50 of the composite microspheres is 60 nm-3100 nm; the particle size distribution index PDI of the composite microspheres is less than or equal to 0.

25.

4. The negative electrode sheet as described in any one of claims 1-3, characterized in that, The inorganic porous material comprises one or more of mesoporous SiO2, boehmite, mesoporous carbon, Al2O3, Li3PO4, and MCM-41 molecular sieve; the particle size Dv50 of the inorganic porous material is 50 nm-3000 nm; the porosity of the inorganic porous material is 65%-90%; and the specific surface area of ​​the inorganic porous material is 450 m². 2 / g-1700 m 2 / g.

5. The negative electrode sheet as described in any one of claims 1-4, characterized in that, The polymer includes one or more of polyacrylic acid, polyethylene glycol, polyvinylidene fluoride, polyurethane, polyimide, and polyvinylidene fluoride-hexafluoropropylene copolymer; the thickness of the coating layer is 1 nm-80 nm.

6. The negative electrode sheet as described in any one of claims 1-5, characterized in that, The negative electrode active layer comprises at least two stacked negative electrode active sublayers; in any two adjacent negative electrode active sublayers, the mass percentage of composite microspheres in the negative electrode active sublayer closer to the current collector is greater than the mass percentage of composite microspheres in the negative electrode active sublayer farther from the current collector.

7. The negative electrode sheet as described in claim 6, characterized in that, The number of negative electrode active sublayers is 2-4.

8. The negative electrode sheet as described in claim 6 or 7, characterized in that, In the negative electrode active layer, the mass percentage of composite microspheres in the negative electrode active sublayer closest to the current collector is 0.5%-1%; the mass percentage of composite microspheres in the negative electrode active sublayer furthest from the current collector is 0.1%-0.25%; and the absolute value of the difference in mass percentage of composite microspheres between any two adjacent negative electrode active sublayers is 0.15%-0.25%.

9. The negative electrode sheet according to any one of claims 6-8, characterized in that, In the negative electrode active layer, the core particle size Dv50 of the composite microspheres in the negative electrode active sublayer closest to the current collector is 50 nm-180 nm; the core particle size Dv50 of the composite microspheres in the negative electrode active sublayer furthest from the current collector is 800 nm-3000 nm; the absolute value of the difference in core particle size Dv50 of any two adjacent composite microspheres in the negative electrode active sublayer is 300 nm-500 nm.

10. The negative electrode sheet according to any one of claims 6-9, characterized in that, In the negative electrode active layer, the thickness of the coating layer of the composite microspheres in the negative electrode active sublayer closest to the current collector is 5 nm-20 nm; the thickness of the coating layer of the composite microspheres in the negative electrode active sublayer furthest from the current collector is 40 nm-80 nm; and the absolute value of the difference in the thickness of the coating layer of the composite microspheres in any two adjacent negative electrode active sublayers is 20 nm-30 nm.

11. The negative electrode sheet according to any one of claims 1-10, characterized in that, The compaction density of the negative electrode sheet is 1.7 g / cm³. 3 -1.8 g / cm 3 ; and / or, the porosity of the negative electrode sheet is 30%-38%; and / or, the saturated liquid absorption capacity of the negative electrode sheet is 0.22 g / g-0.3 g / g; and / or, the liquid absorption rate of the negative electrode sheet is 0.45 g / s-0.75 g / s; and / or, the liquid retention rate of the negative electrode sheet at 25°C is greater than or equal to 93%.

12. A method for preparing a negative electrode sheet, characterized in that, include: At least two negative electrode slurries are provided, each of which includes a negative electrode active material and composite microspheres, and the mass content of the composite microspheres in the at least two negative electrode slurries is different; the composite microspheres include a core and a coating layer disposed on the surface of the core, the core includes an inorganic porous material, and the coating layer includes a polymer; The at least two negative electrode slurries are sequentially coated onto the surface of the current collector to obtain a negative electrode active layer, such that the mass percentage of the composite microspheres in the negative electrode active layer decreases from the side closer to the current collector to the side farther away from the current collector.

13. A battery, characterized in that, The battery includes a positive electrode, a negative electrode, a separator and an electrolyte located between the positive electrode and the negative electrode, wherein the negative electrode includes the negative electrode as described in any one of claims 1-11 or the negative electrode prepared by the method described in claim 12.

14. An electrical appliance, characterized in that, The electrical device includes the battery as described in claim 13.